Development Of Local Government Bureaucracy Capacity To Improve Public Service Performance (Study In Palembang, South Sumatra Province) - M. Yogi Dwi Nalapraya; M. Yoga Jusri Pratama; Akhmad Mustain (MAP Program Pascasarjana Universitas Sjakhyakirti, 2025)
With the establishment of autonomous regions, the distance between public services and the community has narrowed, which is expected to lead to improved service quality. It is also anticipated that all local government stakeholders will experience the benefits more directly. The need and demand for high-quality public services are urgent and must be addressed by the government. Public services should be provided and distributed in accordance with the diverse needs of the state, individuals, residents, communities, and citizens. Therefore, governments have an ongoing obligation to pursue policy innovations to ensure that service delivery meets the various demands of society, thereby improving both quality and impact. This research focuses on the performance of the local government bureaucracy in Palembang City, South Sumatra Province, during the 2023–2024 period. Specifically, it examines public services in four key areas: clean water provision, healthcare, population administration, and licensing services. A qualitative approach with descriptive analysis was employed, comparing the results of interviews with 12 informants against available documented data. The findings indicate that public service performance in Palembang City does not align with the expectations and needs of the community. This underperformance is primarily attributed to the low bureaucratic capacity of the city government, encompassing individual, organizational, and systemic deficiencies. Additionally, weak political will from leadership, limited community participation, and the presence of obstructive structural factors further hinder effective service delivery.